The Effect of Diversity of Board of Directors and Environmental Performance on Corporate Social Responsibility (Empirical Study of Companies Registered at the Ministry of Environment in 2020) - Dhea Vania Dominique Pijoh; Arbi Arsi Ave Noor; Isfi Arininiswah Muawanah; Aditya Prasetyanto; Bima Cinintya Pratama (Proceedings Series on Social Sciences & Humanities, 2022)
The purpose of this study was to determine whether there is a relationship between the diversity of the board of directors and environmental performance in corporate social responsibility. For this study, the population consisted of manufacturing companies traded on the Indonesia Stock Exchange in 2020. Purposive sampling was the method used to collect data so that 71 of the total sample of companies met the requirements. With the help of the SPSS application, descriptive statistical analysis methods were used in the data analysis process. Based on the findings of this investigation, the Corporate Social Responsibility factors are known as the foreign Director, tenure, gender, and environmental performance do not interact with each other at all.